Fierce goodbye [videorecording (DVD)] : living in the shadow of suicide - Collins, Judy, 1939-; Jamison, Kay R.; Buller, Burton (Mennonite Media, 2004)
Over four million people a year in the U.S. mourn the tragic suicide deaths of family members. Suicide devastates family members for many years; family survivors are at greater risk of suicide themselves and the pain ripples out to the entire community. In this video, family survivors reveal their intimate stories and aching pain to assist other survivors and to help the broader community understand the unique and terrible grief of suicide. This documentary explores Protestant, Catholic, Jewish, and Greek Orthodox responses to suicide. The church can be a "healing station" in helping survivors find their way to recovery.